PERAN ORANG TUA DALAM MEMBENTUK KARAKTER PESERTA DIDIK MA NW SENYIUR TAHUN PELAJARAN 2024/2025 - Hafizah, Nur; Sulistio, Iwan; Komaruddin, Komaruddin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to identify and analyze the role of parents in shaping the character of students at MA NW Senyiur. This research is a descriptive qualitative study. Data were collected through observation, interviews, and documentation. The research sample consisted of 18 eighth-grade students. The results of the study show that the role of parents in shaping students’ character can be considered successful, as parents have been directly involved in the process of character education, serving as educators, mentors, supervisors, and companions in developing their children’s character. The supporting factors include parents’ education and knowledge, exemplary behavior in daily life, household harmony, stable economic conditions, and effective communication within the family. The inhibiting factors include a lack of understanding of character education, busyness and limited time for children, negative social environments, and economic and social issues.